2008
DOI: 10.1146/annurev.anchem.1.031207.112953
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Diagnostics for Unraveling Process Chemistry

Abstract: This review focuses on the use of diagnostic tools to examine plasma processing chemistry, primarily plasma species energetics, dynamics, and molecule-surface reactions. We describe the use of optical diagnostic tools, mass spectrometry, and Langmuir probes in measuring species densities, rotational and kinetic energies, and plasma-surface reactions. Molecule-surface interactions for MX(n) species (M = C, Si, N; X = H, F, Cl) are presented and interpreted with respect to the molecule's electronic configuration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 149 publications
1
20
0
Order By: Relevance
“…Although these complimentary measurements cannot directly be compared with the QCLAS results, they provide a means to assess the trends found in the time resolved experiments. Other stable compounds than the precursor molecule CF 4 , namely C 2 F 6 , C 3 F 8 , CHF 3 and HF, were identified in the spectra (CHF 3 and HF are not displayed in figure 8). A linear fit to the calibration spectra yielded the expected distribution of the perfluoroalkanes: n(CF 4 ) > n(C 2 F 6 ) > n(C 3 F 8 ) [9].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although these complimentary measurements cannot directly be compared with the QCLAS results, they provide a means to assess the trends found in the time resolved experiments. Other stable compounds than the precursor molecule CF 4 , namely C 2 F 6 , C 3 F 8 , CHF 3 and HF, were identified in the spectra (CHF 3 and HF are not displayed in figure 8). A linear fit to the calibration spectra yielded the expected distribution of the perfluoroalkanes: n(CF 4 ) > n(C 2 F 6 ) > n(C 3 F 8 ) [9].…”
Section: Resultsmentioning
confidence: 99%
“…No other stable molecules than C 3 F 8 may interfere with CF 4 absorption features in the considered range. Potential contributions of CF 3 and CF radicals (figure 3, lower panel) are negligible due to their weak absorption features or low concentrations. Highly resolved QCLAS spectra of pure CF 4 and C 3 F 8 measured in the discharge vessel (without plasma) are displayed in the lower panel of figure 4.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods most commonly employed rely on mass spectrometry, spectroscopy in different electromagnetic regions and electrical probes [1][2][3]7,28]. Some techniques are suitable to study many different species, but lack the sensitivity to detect the minor ones;…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…[31,33,34] There are several shortcomings of LIF; it is confined to species that possess a fluorescing excited state, requires expensive instrumentation (laser system), and is limited by non-radiative relaxation processes. [35] Notably, recent studies have demonstrated the utility of broadband absorption spectroscopy (BAS) as an alternate technique for probing ground state plasma species. [26,[36][37][38][39][40] Here, we detail a newly constructed combination OES/BAS system for conducting nearly concurrent investigations of both ground and excited state species within NO-containing ICPs.…”
Section: Introductionmentioning
confidence: 99%